The relationship between risk management committee characteristics and modified audit opinion in Malaysia - Suhaimi, Ishak (2015)
The existence of a separate risk management committee (RMC) in non-banking and non-financial companies is seen as very important. It serves as a crucial element in risk management process and as a corporate governance mechanism. This study investigates the relationship between the existence and characteristics of a RMC and modified audit opinion issued by the auditors for the non-banking and non-financial companies listed on Bursa Malaysia. Data is collected from the annual reports of 300 companies for the period of 2004 until 2009. Both descriptive and multivariate analyses are employed to address the research objectives. The results indicate that a separate RMC is negatively related to acceptance of modified audit opinion. Meanwhile, RMC's members with accounting and financial background also reduce the acceptance of modified audit opinion. For RMC's members sitting on more than one board committee, the probability of the company receiving modified audit opinion is higher. Further, companies experiencing modified audit opinion and losses during prior accounting years as well as higher leverage are positively associated with the acceptance of modified audit opinion. Lastly, companies with more than one business segment reduce the acceptance of modified audit opinion. The findings provide empirical evidence on the development and importance of the existence and characteristics of a RMC for the quality of companies' financial reporting. The existence of a separate RMC in non-banking and non-financial companies can reduce the acceptance of modified audit opinion due to risk reasons. Thus, regulators and policy makers need to note the importance of the existence of a separate RMC in nonbanking and non-financial companies as well as some characteristics of the committee that contribute to its success